2007
DOI: 10.1002/ejic.200600946
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Interlayer Arrangement of Transition Metal–Ethylenediaminetetraacetate Complexes Intercalated in Mg/Al Layered Double Hydroxides

Abstract: 2-in LDHs with increasing temperature was studied by variable-temperature in-situ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
3
13
0
Order By: Relevance
“…The positions recorded for the diffraction maxima coincide with those expected for a typical lamellar structure and can be indexed to a hydrotalcite-like structure with R 3̅ m rhombohedral symmetry, , in which case the lowest angle peak corresponds to the basal (003) reflection. The basal spacing is 8.9 Å for ZnAl-NO 3 LDHs, which is similar to the values reported in the literature for LDHs with M 2+ /M 3+ ratios of ∼2 and interlayer NO 3 − anions. , Intercalation of [Eu(EDTA)] − and [Eu(NTA) 2 ] 3− complexes results in the complete disappearance of the (00 l ) reflections of the ZnAl−NO 3 LDHs and an increase in the basal spacing from 8.9 Å in the precursor to 14.5 and 12.5 Å, respectively, as shown by the shift of the (003) reflection to lower angle. The cell parameter a , which represents the average distance between metal cations in the brucite-like sheets and therefore depends on the average ionic radius of the cations, can be calculated from the position of the (110) peak close to 60°.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The positions recorded for the diffraction maxima coincide with those expected for a typical lamellar structure and can be indexed to a hydrotalcite-like structure with R 3̅ m rhombohedral symmetry, , in which case the lowest angle peak corresponds to the basal (003) reflection. The basal spacing is 8.9 Å for ZnAl-NO 3 LDHs, which is similar to the values reported in the literature for LDHs with M 2+ /M 3+ ratios of ∼2 and interlayer NO 3 − anions. , Intercalation of [Eu(EDTA)] − and [Eu(NTA) 2 ] 3− complexes results in the complete disappearance of the (00 l ) reflections of the ZnAl−NO 3 LDHs and an increase in the basal spacing from 8.9 Å in the precursor to 14.5 and 12.5 Å, respectively, as shown by the shift of the (003) reflection to lower angle. The cell parameter a , which represents the average distance between metal cations in the brucite-like sheets and therefore depends on the average ionic radius of the cations, can be calculated from the position of the (110) peak close to 60°.…”
Section: Resultssupporting
confidence: 88%
“…To prepare hybrid LDH materials with precisely tailored functional properties, it is desirable to have detailed knowledge of the arrangement of guest anions intercalated in the interlayer galleries, since the arrangement of interlayer guest anions can dramatically influence the physicochemical properties of LDH materials. , It is well-known that the layer charge density is often an important factor in determining the supramolecular structure of LDHs by virtue of its influence on the guest−host interactions and the loading of the guest anions. Similar effects can be observed by varying the charge density of the interlayer anions, , but no such study of rare earth complexes has been reported to date. Furthermore, calcination of LDHs results in the liberation of physisorbed and interlayer water and the decomposition of hydroxyl layers, which in turn may affect the structure of interlayer complexes.…”
Section: Introductionmentioning
confidence: 99%
“…À with D 3h symmetry. 19,20 It is well known that LDHs have a very strong affinity for carbonate anions; in this case however, no co-intercalation of CO 3…”
Section: Resultsmentioning
confidence: 99%
“…LDH intercalated by EDTA-M complexes ((EDTA-M)-LDH) have been studied previously. These materials have been widely used since they are environmentally friendly, affordable and easily synthesized [31,32]. It has been shown that such intercalates could be developed as heterogeneous catalysts, photocatalytic materials, magnetic nanocomposites, and luminescent materials [31,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%